Embolism resistance explains mortality and recovery of five subtropical evergreen broadleaf trees to persistent drought. Issue 2 (7th December 2022) - Shao, Junjiong; Zhou, Xuhui; Zhang, Peipei; Zhai, Deping; Yuan, Tengfei; Li, Zhen; He, Yanghui; McDowell, Nate G.
Abstract: Subtropical evergreen broadleaf forests (SEBF) are experiencing and expected to suffer more frequent and severe drought events. However, how the hydraulic traits directly link to the mortality and recovery of SEBF trees remains unclear. In this study, we conducted a drought–rewatering experiment on tree seedlings of five dominant species to investigate how the hydraulic traits were related to tree mortality and the resistance and recovery of photosynthesis ( A ) and transpiration ( E ) under different drought severities. Species with greater embolism resistance ( P 50 ) survived longer than those with a weaker P 50 . However, there was no general hydraulic threshold associated with tree mortality, with the lethal hydraulic failure varying from 64% to 93% loss of conductance. The photosynthesis and transpiration of tree species with a greater P 50 were more resistant to and recovered faster from drought than those with lower P 50 . Other plant traits could not explain the interspecific variation in tree mortality and drought resistance and recovery. These results highlight the unique importance of embolism resistance in driving carbon and water processes under persistent drought across different trees in SEBFs. The absence of multiple efficient drought strategies in SEBF seedlings implies the difficulty of natural seedling regeneration under future droughts, which often occurs after destructive disturbances (e.g., extreme drought events and typhoon), suggesting that this biome may be highly vulnerable to co‐occurring climate extremes.